Antimicrobial treatment duration for uncomplicated bloodstream infections in critically ill children: a multicentre observational study - Sandra Pong; Robert A. Fowler; Srinivas Murthy; Jeffrey M. Pernica; Elaine Gilfoyle; Patricia Fontela; Asgar H. Rishu; Nicholas Mitsakakis; James S. Hutchison; Michelle Science; Winnie Seto; Philippe Jouvet; et al. (BMC, 2022)
Abstract Background Bloodstream infections (BSIs) cause significant morbidity and mortality in critically ill children but treatment duration is understudied. We describe the durations of antimicrobial treatment that critically ill children receive and explore factors associated with treatment duration. Methods We conducted a retrospective observational cohort study in six pediatric intensive care units (PICUs) across Canada. Associations between treatment duration and patient-, infection- and pathogen-related characteristics were explored using multivariable regression analyses. Results Among 187 critically ill children with BSIs, the median duration of antimicrobial treatment was 15 (IQR 11-25) days. Median treatment durations were longer than two weeks for all subjects with known sources of infection: catheter-related 16 (IQR 11-24), respiratory 15 (IQR 11-26), intra-abdominal 20 (IQR 14-26), skin/soft tissue 17 (IQR 15-33), urinary 17 (IQR 15-35), central nervous system 33 (IQR 15-46) and other sources 29.5 (IQR 15-55) days. When sources of infection were unclear, the median duration was 13 (IQR 10-16) days. Treatment durations varied widely within and across PICUs. In multivariable linear regression, longer treatment durations were associated with severity of illness (+ 0.4 days longer [95% confidence interval (CI), 0.1 to 0.7, p = 0.007] per unit increase in PRISM-IV) and central nervous system infection (+ 17 days [95% CI, 6.7 to 27.4], p = 0.001). Age and pathogen type were not associated with treatment duration. Conclusions Most critically ill children with BSIs received at least two weeks of antimicrobial treatment. Further study is needed to determine whether shorter duration therapy would be effective for selected critically ill children.